Andrographolide Induces Noxa-Dependent Apoptosis by Transactivating ATF4 in Human Lung Adenocarcinoma Cells - Zhang, Junqian; Li, Chunjie; Zhang, Li; Heng, Yongqing; Xu, Tong; Zhang, Yunjing; Chen, Xihui; Hoffman, Robert M; Jia, Lijun (Frontiers in Pharmacology, 2021)
Lung adenocarcinoma is the most common pathological type of lung cancer with poor patient outcomes; therefore, developing novel therapeutic agents is critically needed. Andrographolide (AD), a major active component derived from the traditional Chinese medicine (TCM) Andrographis paniculate, is a potential antitumor drug, but the role of AD in lung adenocarcinoma remains poorly understood. In the present study, we demonstrated that AD inhibited the proliferation of broad-spectrum lung cancer cell lines in a dose-dependent manner. Meanwhile, we found that a high dose of AD induced Noxa-dependent apoptosis in human lung adenocarcinoma cells (A549 and H1299). Further studies revealed that Noxa was transcriptionally activated by activating transcription factor 4 (ATF4) in AD-induced apoptosis. Knockdown of ATF4 by small interfering RNA (siRNA) significantly diminished the transactivation of Noxa as well as the apoptotic population induced by AD. These results of the present study indicated that AD induced apoptosis of human lung adenocarcinoma cells by activating the ATF4/Noxa axis and supporting the development of AD as a promising candidate for the new era of chemotherapy.